Local species richness of parasitoid wasps (Ichneumonidae: Pimplinae) in Afrotropical forest: Conservation perspectives - Österman, Emil M.; Hopkins, Tapani; Sääksjärvi, Ilari E. (Wiley, 2026)
Effective conservation of biodiversity relies on an understanding of its composition and distribution. Parasitoid wasps are an ecologically important and highly species-rich group of Hymenoptera but are poorly known in the tropics. One strategy for conserving their richness is based on finding out how the richness is distributed in different habitats.
Here, we investigate the local species richness and biological composition of parasitoid wasps (Ichneumonidae: Pimplinae) collected with Malaise traps in Ugandan tropical forest. We link the richness of Pimplinae and its four biological groups to habitat types across a successional gradient.
We found higher pimpline richness in forest than in nearby farmland, with the highest richness in the group of idiobiont parasitoids of weakly concealed hosts.
Our results suggest that protecting primary tropical forest may be particularly important for conserving a high richness of koinobiont ectoparasitoids of spiders and that nearby disturbed forest can have high parasitoid wasp richness after a few decades of regeneration.
Trapping in forest collected 5623 individuals of 83 species, which is high compared with pimpline richness at temperate latitudes, supporting a typical latitudinal diversity gradient of at least the Pimplinae subfamily of Ichneumonidae.